Developing innovative humanising entrepreneurship education programme for youth employment in Malaysia - Ahmad Kamal Ariffin, Ahmad Luqman; Ahmad Dahlan, Abdul Rahman; Mhd Sarif, Suhaimi (Research Publish Journals, 2019)
Education for youth is the most powerful tool to change the world. It plays a significant role to design the future as a successful citizen in society. The United Nation’s Sustainable Development Goals in quality education focus on increasing the number of youth having relevant knowledge and skills, including technical and vocational skills for self-employment or employment. Youth problems are commonly encountered for those who are poor, needy and unemployed. Hence, this paper aims to provide a conceptual humanising education business model including an eLearning, mentoring system and eMarketplace to help these youths in Gombak District, Selangor. Through humanising education development business model, this programme will enhance knowledge, skills and values. It also creates job and entrepreneurship, a platform to generate income and wellbeing of youth community. The findings show that this programme has potential to improve the quality education, strengthen the economy and improving social status of youth with Islamic values. To achieve the objectives of this study, the business modelling tools like the Business Model Canvas and Value Proposition Canvas are used. Business model canvas is to visualize holistic view of all the building blocks of starting a business including customer segments, value propositions and revenue streams. Then, value proposition canvas is required to ensure that the programme is positioned around what the customer’s values and needs, pains, gains and job-to-do. This paper adapted design thinking approach that draws an iterative process in which to understand the user’s pain, challenge assumptions,redefine problems and formulate strategies and conceptual business model.